Content validity evidence of the Brazilian version of the Cognitive Symptom Checklist-Work-21 - Elaine Cristina Lopes da Rocha; Kayo Henrique Jardel Feitosa Sousa; Paola Alves de Oliveira Lucchesi; Magda Guimarães de Araujo Faria; Marcos Alencar Abaide Balbinotti; Flavio Rebustini; Renata Eloah de Lucena Ferretti-Rebustini; Cristiane Helena Gallasch (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to cross-culturally adapt and assess the content validity evidence of the Cognitive Symptom Checklist-Work-21 for the Brazilian context. Method: a psychometric study of cross-cultural adaptation, covering the stages of translation, reconciliation, back-translation, intercultural equivalence assessment and content validity evidence analysis, considering Content Validity Ratio parameters in breast cancer survivors. Results: the translations were equivalent to the original version. Colloquial expressions were modified, tense, verbal adjusted, and two items containing multiple commands were separated. The final version now contains 22 items, presenting semantic, conceptual, idiomatic and experimental equivalences. The pre-test indicated good understanding and ease in the response process. Conclusion: the final version was defined as "Lista de verificação de sintomas cognitivos relacionados ao trabalho - 22 itens", showing good linguistic equivalence and strong evidence of content validity in the Brazilian context.